Integrative omics analysis in Pandanus odorifer (Forssk.) Kuntze reveals the role of Asparagine synthetase in salinity tolerance - Rashmi, Deo; Barvkar, Vitthal T.; Nadaf, Altafhusain; Mundhe, Swapnil; Kadoo, Narendra Y. (Scientific Reports, 2019)
Pandanus odorifer (Forssk) Kuntze grows naturally along the coastal regions and withstands salt-sprays as well as strong winds. A combination of omics approaches and enzyme activity studies was employed to comprehend the mechanistic basis of high salinity tolerance in P. odorifer. The young seedlings of P. odorifer were exposed to 1 M salt stress for up to three weeks and analyzed using RNAsequencing (RNAseq) and LC-MS. Integrative omics analysis revealed high expression of the Asparagine synthetase (AS) (EC 6.3.5.4) (8.95 fold) and remarkable levels of Asparagine (Asn) (28.5 fold). This indicated that salt stress promoted Asn accumulation in P. odorifer. To understand this further, the Asn biosynthesis pathway was traced out in P. odorifer. It was noticed that seven genes involved in Asn bisynthetic pathway namely glutamine synthetase (GS) (EC 6.3.1.2) glutamate synthase (GOGAT) (EC 1.4.1.14), aspartate kinase (EC 2.7.2.4), pyruvate kinase (EC 2.7.1.40), aspartate aminotransferase (AspAT) (EC 2.6.1.1), phosphoenolpyruvate carboxylase (PEPC) (EC 4.1.1.31) and AS were up-regulated under salt stress. AS transcripts were most abundant thereby showed its highest activity and thus were generating maximal Asn under salt stress. Also, an up-regulated Na+/H+ antiporter (NHX1) facilitated compartmentalization of Na+ into vacuoles, suggesting P. odorifer as salt accumulator species.

Role of ions and their transporters in combating salt stress in Pandanus odorifer (Forssk.) Kuntze - Rashmi, Deo; Ansari, Waquar A.; Kadoo, Narendra Y.; Barvkar, Vitthal T.; Deshmukh, Rupesh; Nadaf, Altafhusain B. (Acta Physiologiae Plantarum, 2023)
Soil salinity is a major environmental constraint causing huge losses in crop production. Pandanus odorifer (Forssk.) Kuntze is an aromatic monocot plant species belonging to the family Pandanaceae, which grows naturally on the saline soils along the coasts of Asia, Southeast Asia, and Polynesia. The plants are dioecious and highly fertile, and the consistent saline sprays, strong winds, and severe soil salinity hardly affect their growth and fertility. Hence, understanding the mechanism of high salinity tolerance in P. odorifer could provide major advances in overcoming salinity stress in crop plants. In the present study, we analyzed control (0 M NaCl) and treated (1 M NaCl treatment for 3 weeks) plants of P. odorifer to understand the role of ion distribution, ion transport, and related mechanisms under salt stress. Using a combination of ionomics and transcriptomics approaches, we identified the molecular mechanisms contributing to the high salinity stress in P. odorifer. Under NaCl stress, there was a significant increase in Na, Cl, and other ions in leaves, while the concentrations of Si, Fe, Ni, and Ti decreased. Similarly, in roots, the levels of Na, Mg, Cd, and Cr were significantly high, while the levels of other ions decreased. Most of the genes related to ion transport and homeostasis, such as NHX1, CLC-C, SOS1, HAK, and ABC transporters, were upregulated in 1 M NaCl stress conditions. This study revealed that vacuolar sequestration of Na+ and the distribution of ions in the roots and shoots play significant roles in the salt-stress tolerance mechanism of P. odorifer.
Keywords: Ion transport; Ionomics; Pandanus; Salinity tolerance; Transcriptomics; Vacuolar sequestration

Harnessing microRNAs and their targets for salt stress tolerance in Pandanus odorifer - Rashmi, Deo; Barvkar, Vitthal T.; Nadaf, Altafhusain B.; Kadoo, Narendra Y. (Journal of Plant Biochemistry and Biotechnology, 2025)
Salinity poses a formidable challenge to agriculture, detrimentally impacting plant growth and the yield of several crops globally. Pandanus odorifer (Forssk.) Kuntze is a highly salt-stress resilient plant that grows naturally along the coastal regions of Asia, Southeast Asia, and Polynesia. It is frequently found as a frontier species along the sandy shores receiving constant salt sprays. MicroRNAs (miRNAs) play essential regulatory roles in growth, development, and combating various biotic and abiotic stresses. Thus, characterizing miRNAs and their targets is critical to understanding their roles in salt stress tolerance. Through a rigorous analysis based on homology, secondary structure and signatures of other miRNA genes, we identified 52 conserved nonredundant miRNAs from the P. odorifer transcriptome data. These miRNAs were diverse and belonged to 23 miRNA phylogenetic families. Several miRNAs, including pod-MIR156a, pod-MIR164d, and pod-MIR535d, demonstrated distinct expression patterns in response to salt stress. Their target genes exhibited opposing expression trends, corroborating the intricate miRNA-target relationship. Delving deeper into their influence, we discovered that these miRNAs mainly targeted transcription factors that are known for their pivotal roles in stress responses. We also detected four miRNA-star (miRNA*) sequences (the complementary strands of functional mature miRNAs), which supports the authenticity of the identified miRNAs. This study unveils the intricate regulatory mechanism through which miRNAs may reinforce salt stress tolerance in P. odorifer, providing a promising avenue for enhancing crop resilience to various stresses through miRNA-based strategies.
Keywords: Abiotic stress; microRNA; miRNA targets; Salinity tolerance; salt stress; Transcription factors